Synergistic Connection Between Mechanisms Of Administrative Leadership And Strategic Thinking And Their Role In Developing The Creative Capabilities Of Iraqi Private Banks - Khaled Mehdi, Eyad; Kamil Oudah, Bilal (Opción, 2019)
The research included the formation of clear perceptions about creative abili- ties through the continuity of the relationship between management leadership and strategic thinking. The research adopted the method of analytical survey of (114) managers in three private banks to ensure the availability of creative capabilities using statistical means. The results show that there is an increase in the role of management leadership mechanisms in enhancing creative ca- pabilities through the possibilities of strategic thinking, as they increase the effectiveness of creativity in all directions to achieve the effective organization or creative organization. Based on this, a set of conclusions were reached that recommend the introduction of strategic thinking mechanisms as a platform for action in banking environment and utilization of innovative capabilities.